Chemical Diversity and Biochemical Transformation of Biogenic Organic Sulfur in the Ocean - Tang, Kai (Frontiers in Marine Science, 2020)
Organic sulfur compounds are not only essential for organismal survival but also indispensable for the sulfur cycle. Over the past few decades, dimethylsulfoniopropionate (DMSP) and dimethyl sulfide (DMS) cycling in the upper ocean have been well characterized from the genetic to the ecosystem level. Recent advances in the study of marine sulfonate transformation have indicated that phytoplankton and microbes play key roles in oceanic sulfur and carbon fluxes. This review provides biochemical details of the major sulfur metabolites, and presents an interlinked reaction network with genetic information on the microbial transformation and mineralization of sulfur compounds. This review also discusses future prospects for the discovery and characterization of novel substrates and enzymes involved in organosulfur cycling, as well as for investigations of deep sea and sedimentary organic sulfur.